PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2015 - -, Fifi Nofitasari (EKONOMIA, 2019)
This study aims to prove: (1) Is there a positive and significant influence between cash turnover on profitability in plastic and packaging companies listed on the Indonesia Stock Exchange in 2014-2015? (2) Is there a positive and significant influence between accounts receivable turnover on profitability in plastic and packaging companies listed on the Indonesia Stock Exchange in 2014-2015? (3) Is there a positive and significant influence between inventory turnover on profitability in plastic and packaging companies listed on the Indonesia Stock Exchange in 2014-2015? (4) Is there a simultaneous and significant positive influence between cash turnover, accounts receivable turnover, inventory turnover on profitability in plastic and packaging companies listed on the Indonesia Stock Exchange in 2014-2015. The data collection method used in this study is with or research 2 consecutive years, the method of documentation carried out by collecting and recording data relating to research variables, in this case the company's Annual Financial Report for the Plastic and Packaging sub-sector on the Stock Exchange Indonesia during the 2014-2015 study period. After using financial ratio calculations, statistical statistical tests using sample t test and sample f test were conducted to test three pairs of samples to find out whether the three had a positive and significant effect.The results of the study on the Effect of Cash Turnover, Accounts Receivable Turnover, Inventory Turnover on Profitability concluded that the calculation uses financial ratios and sample t test and sample test f, it is known that there is no positive and significant influence on profitability. These hypotheses are rejected